Structural functions of the permittivity field of a statistically anisotropic troposphere - Шиляева, О.Л.; Петров, В.А. (Radiotekhnika, 2012)
Structural functions of the air permittivity field in the surface layer of the troposphere, taking into account the statistical inhomogeneity and the layered structure are investigated. It is shown that there are at least two regions of local homogeneity for small and large scales. Integral scale heterogeneities in these areas differ by one or two orders of magnitude.